Analysis of small-scale topology and macroscale mechanical properties of shape memory chiral-lattice metamaterials. (15th April 2021) - Zhao, Wei; Zhu, Jie; Liu, Liwu; Leng, Jinsong; Liu, Yanju
Abstract: Chiral-lattice metamaterials with unique mechanical, optical, electrical and magnetic properties have been widely used in many engineering applications, such as chiral recognition and separation, stealth materials and devices, as well as biological sensors. Various design strategies have been developed to obtain chiral-lattice metamaterials with different mechanical properties. The fast grown design strategies that can provide a variety of Poisson's ratios and elastic moduli have brought new opportunities to emerging biomedical applications. In this study, hexagonal and tetragonal chiral-lattice metamaterials with positive and negative Poisson's ratios were designed. The design strategy was based on a network structure with a periodic lattice topology, which was formed by three outer rings connected to the central ring via ligaments. The wide applications of this type of metamaterial were investigated via experiments and finite-element analysis. Demonstrative examples and the shape-memory effect (SME) suggest that the chiral-lattice structure has great potential in developing programmable metamaterials. The findings of this study provide essential guidance for the design of chiral network structures with the desired mechanical properties.